Complete mtDNA genomes of Anopheles darlingi and an approach to anopheline divergence time - Moreno, Marta (2020)
Background: The complete sequences of the mitochondrial genomes (mtDNA) of members of the northern and southern genotypes of Anopheles (Nyssorhynchus) darlingi were used for comparative studies to estimate the time to the most recent common ancestor for modern anophelines, to evaluate differentiation within this taxon, and to seek evidence of incipient speciation. Methods. The mtDNAs were sequenced from mosquitoes from Belize and Brazil and comparative analyses of structure and base composition, among others, were performed. A maximum likelihood approach linked with phylogenetic information was employed to detect evidence of selection and a Bayesian approach was used to date the split between the subgenus Nyssorhynchus and other Anopheles subgenera. Results: The comparison of mtDNA sequences within the Anopheles darlingi taxon does not provide sufficient resolution to establish different units of speciation within the species. In addition, no evidence of positive selection in any protein-coding gene of the mtDNA was detected, and purifying selection likely is the basis for this lack of diversity. Bayesian analysis supports the conclusion that the most recent ancestor of Nyssorhynchus and Anopheles+Cellia was extant ∼94 million years ago. Conclusion: Analyses of mtDNA genomes of Anopheles darlingi do not provide support for speciation in the taxon. The dates estimated for divergence among the anopheline groups tested is in agreement with the geological split of western Gondwana (95 mya), and provides additional support for explaining the absence of Cellia in the New World, and Nyssorhynchus in the Afro-Eurasian continents. © 2010 Moreno et al; licensee BioMed Central Ltd.